Análise do uso da água para irrigação na bacia hidrográfica do Rio Formoso - Fagundes, Fabiano (Universidade Federal do Tocantins, 2022)
With the imminent possibility of water scarcity for a nearby scenario, it is essential to carry out studies that propose reliable parameters for water management. In the hydrographic basin of the Formoso river, there is an intense production of rice in the rainy season and, secondarily, in the dry season, soybeans are cultivated for seed. In order to maintain the cultivation of soy during this period, it is necessary to remove water from the region's rivers, which annually undergo water stress. In this sense, this work presents an analysis of the use of water for irrigation of eighteen projects located in the hydrographic basin of the Formoso river, during the soybean planting period in the 2019 crop year, through relative coefficients of water productivity. The analysis was possible due to the availability of real data on water resource capture for irrigated agriculture, from the Institute of Attention to Cities / High Level Management, as well as data from the Public Ministry of Tocantins, National System of Rural Environmental Registration, as well as the CAR Management Information System of the state of Tocantins. Once the database was arranged, georeferenced images of agricultural production monitoring were produced by the NDVI method to establish relation parameters such as: volume of water abstracted by estimated production, volume of water abstracted by the irrigated area, extension of channels by the irrigated area and volume of water collected by extension of channels. As a result, it can be inferred that 72 % of the enterprises practiced irrigation after the second half of August, considered by specialists as a critical fact to the conditions of the Formoso river basin, as well as disparities in relation to the days of abstraction are pointed out, showing a variation of 335 %. In verifying the net irrigation depth for soybean production, there was a difference of 839 % between the lowest and the highest catchment value. As for the coefficients, it was possible to point out a variation of: 859 % for the volume of water abstracted by the estimated production, 927 % for the volume of water abstracted by the irrigated area, 552 % for the extension of channels by the irrigated area and 3,000 % for the volume of water collected by extension of channels. Finally, the factors that could possibly cause variations in the coefficients found were discussed.